The strategy of financial pressure - Grant, Alexander Thomas Kingdom (London, Macmillan, 1972)
This book examines the effects of the continuous application of financial pressure on the contemporary U.K. economy
Includes bibliographical references.
obn22/01/2019
Loans
Keywords: Finance, Public; Fiscal policy; Monetary policy